The impact of digital finance on young People’s health insurance participation decisions in China - Chai, Mengran; Wu, Lin (Frontiers in Public Health, 2024)
Background The digital finance era has reshaped young people’s lifestyles, risk perceptions and insurance participation decisions. Modern youth have to constantly seek for rational social security support and construct individual protection barriers to adapt to new lifestyles and social structures. China’s multi-tiered, universal health insurance system is urgently needed to satisfy young people’s flexible needs and rational decision-making. Methods Based on the micro data from 2011 2021 Chinese General Social Survey (CGSS), this paper uses macro data from Digital Inclusive Finance Index (DIFI) matching to construct probit and m-logit model to assess the impact of the development of digital finance on Chinese youth whether or not to participate in health insurance, and how they choose the concrete type of health insurance. Results (1) Baseline regression results shows that digital finance has a significant positive effect on Chinese youth’s health insurance participation decisions, and has different effects on choices within health insurance types. Strong support for the conclusions is provided by endogeneity and robustness tests. (2) The results of the heterogeneity analysis reveal that the marginal effect of digital finance on young people’s health insurance decisions shows urban–rural differences, divergence in levels of self-rated health. (3) The mechanism analysis results suggest that there are two mechanism paths of digital finance on youth health insurance decisions: the household income effect and the subjective well-being effect, and two moderating effects: employment type and family structure. Conclusion Highlighting the positive value that digital finance brings to the perception of youth insurance participation and the construction of social security systems, it needs to pay close attention to the dynamic changes in employment security and family structure through data, and explore the socio-psychological fluctuation and demand for social security among modern youth. To provide a way forward to achieve the integration of the health insurance system in China and solve the current problem of health insurance equity.